Advancing Graduate in Private Universities; Developing Graduate Employability for a Challenging Labor - Kusmawan, Asep; Makbulloh, Deden; AD, Yahya; Amiruddin, Amiruddin (JURNAL AL-TANZIM, 2023)
This study aims to analyze the formulation of improving the quality of graduates carried out by universities in facing the world of work challenges. A qualitative case study type approach is used in this study. Interviews, observations and documentation are used as data collection media. The data analysis was carried out systematically, starting from data reduction, data presentation and conclusion. The study results show that the formulation of improving the output quality of STAI Al Maarif Way Kanan is carried out through planning, implementing and evaluating the quality improvement of graduates in a planned and systematic way with the principle of continuous improvement. This research provides implications for the importance of strategic management to create graduates who are competitive and ready to use.